DECLARATIVE AND PROCEDURAL KNOWLEDGE IN TEACHING GRAMMAR - Suroso, Bambang (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2018)
When one has to teach a language, he should possess a vlew of what languages. One possibility is to view language as a skill. Therefore language learning is comparable to other types of cognitive skill acquisition. ln this case, there is a need for us to understand the concept of declarative and procedural knowledge. This is similar to that of knowledge about and knowledge how or knowledge and control (Bialystok, in Johnson, 1994), competence and performance, and usage and use. The first of those terms refers to factual knowledge of a language such as grammar, vocabulary, pronunciation etc., and the latter to the actual use of the knowledge in real act of communication such as in speaking, reading, listening and writing. The problem is how these two knowledge can be developed. This paper is inspired by Keith Johnson whose Teaching Declarative and Procedural knowledge suggest that the strategy to develop the knowledge correspond to what is commonly called learning and acquisition.